Assessing the Quality of Higher Education Website and Its Influential Factors - Brillian, Muhammad Teguh; Ananda, Fachri (Fakultas Sains dan Teknologi UIN Imam Bonjol Padang, 2021)
This qualitative research is aim to evaluate the quality of Faculty of Science and Technology UIN Imam Bonjol Padang’ website. We adopt Webqual 4.0 to measure the quality, then mapping the result into Importance-Performance Analysis Quadrant to obtain which attribute should be prioritized for improvement. The gap between expectation and performance of the website is -0.126 which shows that the website does not meet the visitor expectation yet. Further, four attribute should be prioritized for improvement, namely attractive appearance, appropriate design related to the type of website, information relevance, and conveys a sense of community.